If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 10) = 59 Reorder the terms: (10 + x) = 59 Remove parenthesis around (10 + x) 10 + x = 59 Solving 10 + x = 59 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = 59 + -10 Combine like terms: 10 + -10 = 0 0 + x = 59 + -10 x = 59 + -10 Combine like terms: 59 + -10 = 49 x = 49 Simplifying x = 49
| (3x/8)-(7x/16) | | 4(2)-9=7(2)+3 | | 6x+5=13x-75 | | x=3(10-x)/4 | | 3x/8-7x/16 | | 74+x=90 | | 28b+6=16b | | 4x=3(10-x) | | 9x+21=5x+93 | | 4x=30-3x | | x-4/6=9 | | 115-3x=24x+22 | | 5a+y=180 | | 5=9+10y | | c=2*7.08*3.14 | | 9=2g-5 | | 7(2y+6)=4y+72 | | (2x-3)=(3x-5) | | 10x^6+8x^4=0 | | x=27+-2x | | x-10/x+2=7 | | -2.7=-1.3+0.7x | | x-(8x^(1/2))+4=0 | | 8/11(n+10)=64 | | -3x+12=9 | | 9-y=9 | | 15x-45+3x=18x+18-13 | | x+0.07x=16.05 | | 9x-1=8x+19 | | (9x+2)/5=4 | | (3x^2+2x-9)-(-3x+4)= | | -3-y=9 |